Transforming Arabic Language Teaching Through Digitalization For Non-Arabic Learners - Muhammad Rido’i; Laili Mas Ulliyah Hasan; Nada Ibrahim Alribdi; Muhammad Tareh Aziz (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2025)
This study explores the transformation of Arabic language teaching through online digitalization for non-Arab learners at the MaliQa Arabic Language Academy. The main objective is to examine the impact of digital technology on learners' motivation, learning outcomes, and the challenges faced during the online learning process. The research employs a qualitative approach using phenomenological methods, with data collected through observations, interviews, and documentation. The findings reveal that the use of digital platforms such as Google Meet and learning media like PowerPoint enhances student motivation by offering time flexibility, interactive features, and engaging visual presentations. However, technical barriers such as network instability and limited access to devices, as well as challenges related to digital literacy, were also identified as obstacles to effective learning. The study concludes that while digitalization offers significant advantages in improving the quality of Arabic language instruction, adequate infrastructure support and digital literacy training are essential to optimize the effectiveness of online learning.